Synthesis and characterization of hypercoordinated silicon anions: catching intermediates of lewis base catalysis - Ansmann, Nils; Hartmann, Deborah; Sailer, Sonja; Erdmann, Philipp; Maskey, Rezisha; Schorpp, Marcel; Greb, Lutz (Angewandte Chemie. International edition, 2022)
Anionic hypercoordinated silicates with weak donors were proposed as key intermediates in numerous silicon-based reactions. However, their short-lived nature rendered even spectroscopic observations highly challenging. Here, we characterize hypercoordinated silicon anions, including the first bromido-, iodido-, formato-, acetato-, triflato- and sulfato-silicates. This is enabled by a new, donor-free polymeric form of Lewis superacidic bis(perchlorocatecholato)silane 1. Spectroscopic, structural, and computational insights allow a reassessment of Gutmann's empirical rules for the role of silicon hypercoordination in synthesis and catalysis. The electronic perturbations of 1 exerted on the bound anions indicate pronounced substrate activation.
Version of record online: May 5, 2022
Gesehen am 04.10.2022